Research skills in the first-year biology practical - Are they there? - Torres, Lyn (Journal of University Teaching and Learning Practice, 2018)
Laboratory practicals engage students in complex thinking to build their scientific knowledge and understanding. Surprisingly few studies connect the development of students’ cognitive and metacognitive skills for learning in the laboratory practical with foundational skills for researching. Librarians strive to establish teaching partnerships with academics to contextualise research skills within curriculum content. However, pedagogical models to make research skills explicit and guide library-faculty collaborations are lacking. This study explores the Research Skill Development (RSD) framework (Willison & O’Regan 2006/2018; see the first article in this issue) to extrapolate students’ research skills in a first-year biology practical unit. A qualitative research design was applied to identify research skills in the unit’s laboratory manual and in descriptive observations of students in five laboratory practicals. Results show students engaged in the research skills articulated by the RSD, yet these skills were implied rather than explicitly taught. Implications suggest that fundamental research skills which enable student preparedness for research can be overlooked in practical curricula. Research skills remaining unrecognised impacts learning and teaching, including the contribution librarians could make in this context. Findings demonstrated that the RSD is a useful theoretical construct and a priori framework to make research skills visible to educators.